The Cultural Psychological Impact of Educators’ Identity on the Concept of International-Mindedness in the International Baccalaureate Program - Udju, Ineke (Comparative and International Education / Éducation comparée et internationale, 2025)
⁠⁠⁠⁠⁠⁠⁠This work examines the International Baccalaureate (IB) program’s concept of international-mindedness and its application to school cultures at the International School of Prague. Its objective is to analyze the concept of international-mindedness with three different levels of identifiers (educator-self, educator-self vs. students, educator-self vs. outside school environment) to express that the nebulous and equivocal educator identity in international school(s) is veritably more complex than what is defined by the IB. Two approaches to identity in individualist and collectivist societies will be discussed to understand the identity of educators. Based on interviews with four educators at the International School of Prague, this article shows that separating “international-mindedness” from “international” can create conflicting identities among educators, particularly between individualist and collectivist self-identities, and it ultimately concludes that no sole international mind exists due to the dialectical and exclusionary nature of various international-mind identifications.